(untitled) (Fiep Bulletin - online, 2016)
This study analyzed the evaluative Physical Education Reform of Secondary Education of Rio Grande do Sul, in action in the state management of 2011-2014, which replaced the qualitative evaluation system (for notes and newsletters) by qualitative (with references and opinions) , intending a more democratic and emancipator evaluation. To do so, we delimited a qualitative case study of entering into the "floor" of a school network and establishing seven subjects of the faculty of an institution’s network, three of Physical Education, besides the direction and pedagogical supervision.